EFEK VARIASI WAKTU BALL MILLING TERHADAP KARAKTERISTIK ELEKTROKIMIA SEL SUPERKAPASITOR BERBASIS KARBON - Fitria Puspita Sari; Erman Taer; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Supercapacitor electrodes from rubber wood saw dust (RWSD) have been fabricated using experiment method to study the ball milling variation time on performance of the supercapacitor cells. The carbon electrodes were prepared with time variation of 20, 40, and 80 hours and thickness of 0.2 mm. Carbon electrodes were carbonized at 600oC and followed by physical activation method in CO2 gas atmosphere on the constant temperature of 900o C, and chemical activation was performed by KOH as an activating agent. Densities of the electrodes were 0.849 g/cm3 , 0.892 g/cm3 , 0.982 g/cm3 respectively. XRD measurement showed the peaks of carbon electrodes at 2θ of 24.091o and 44.473o which represented the presence of carbon materials with their crystal orientation of (002) and (100). SEM micrograph on magnification of 1000X showed that the pore distribution of the carbon electrodes dominant on macropores. This study found that the effects of increasing of ball milling time influenced the electrochemical properties of supercapacitor electrodes fro m RWSD. The optimum supercapacitor performance was found on 20 hour milling time electrode and had a specific capacitance of 55.414 F/g.